Costumed doubles and avatars in Janieta Eyre’s photographic self-portraits - Valérie MORISSON (E-REA)
This article aims at furthering our understanding of costuming in self-portraiture through the analysis of Janieta Eyre’s photographic works. Exploring the fictionalizing potentialities of photography and flouting the conventions of self-portraiture, the Canadian artist stages her multiple doubles in a playful yet introspective way. The studio becomes an experimental huis-clos harbouring fantasy self-explorations. The costumes that she assembles allow for complex dramatizations of the othered self. In these performative self-fictions the costume constitutes a prosthetic device. Her burlesque impersonations address gender identity in a subversive way. Judith Butler’s view of gender as stylized repetition of acts chimes in with Eyre’s use of seriality and endless mises-en-abyme, while Paul Gee’s definition of projective identity as a liminal form of identity—an interface between the real and the virtual self—and other researchers’ exploration of the avatar in game theory shed additional light on Eyre’s use of costuming.